Strategi Politik Luar Negeri Indonesia dalam Upaya Mitigasi Pandemi Global COVID-19 - Hanifahturahmi Hanifahturahmi (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2021)
This research aims to analyze Indonesia's foreign policy strategy to mitigate the global COVID-19 pandemic and the factors that affect Indonesia's foreign policy strategy. This research uses the perspective of behavioralism with the level of nation-state analysis. The method used in this research is qualitative research methods. The results show that Indonesia's foreign policy strategy in mitigating the global COVID-19 pandemic is through Alliance for Multilateralism that focuses on two things. First, the Indonesian government seeks to protect Indonesian citizens abroad. Second, the Indonesian government encourages strengthening governance within the framework of global health by supporting policies issued by WHO and establishing good cooperation, regionally and multilaterally. The factors that influence Indonesia's foreign policy strategy in efforts to mitigate the global COVID-19 pandemic are Indonesia's national interests and the international political constellation. Indonesia's national interests focus on protecting Indonesian citizens both at home and abroad. Meanwhile, the international political constellation has increased conflicts due to mutual suspicion between developed countries that are involved in trade competition in the health industry.